Pengaruh Pemberian Pupuk Hayati Mikoriza dan NPK Terhadap Petumbuhan dan Perkembangan Tanaman Sawi Manis (Brassica juncea L.) - Harahap, Khofifa Khairani; Zulfida, Ida; Miyarnis, Miyarnis (JURNAL AGROPLASMA, 2024)
Mustard greens ( Brassica juncea L.) is one of the horticultural plant commodities from the type of vegetables whose young leaves are used as vegetable food and have various benefits and uses. In people's lives, they consume three types of mustard greens, namely: white mustard greens, green mustard greens, and pak choy mustard greens. . This research was conducted in May 2024 - July 2024, in the experimental garden land of the Faculty of Agriculture, Indonesian Community Development University (UPMI) Medan, Jl. Balai Desa Pasar 12 Marindal II, Patumbak District, Deli Serdang Regency, North Sumatra Province. The materials used in this study were mini mustard seeds, biological fertilizers and NPK fertilizers . While the tools were watering cans, meters, hoes, machetes, knives, plastic ropes, scales, and stationery. This study was conducted using a Factorial Randomized Block Design (RAK) consisting of two factors, namely: Factor I is the provision of mycorrhizal biological fertilizer (H) consisting of 3 levels, namely H 0 (Without Provision of Mycorrhizal Fertilizer), H 1 (10gr/plant Mycorrhizal Fertilizer), H 2 (20gr/plant Mycorrhizal Fertilizer). While Factor II is the provision of NPK fertilizer, namely N 0 (Without Provision of NPK Fertilizer), (N 1 1gr/plant NPK Fertilizer), (N 2 1.3gr/plant NPK Fertilizer). The single effect of mycorrhizal fertilizer (H) at the H 2 (20 g/plant) has an effect on increasing plant height (cm) while the number of leaves (blades) has an effect at the age of 4 weeks after planting, and has an effect on the wet weight (g) of the plant. While the single application of NPK fertilizer (N) at the N 2 level (1.3 g/plant) has an effect on increasing plant height (at the ages of 2 weeks after planting, 3 weeks after planting, and 4 weeks after planting), on the number of leaves (at the ages of 2 weeks after planting, 3 weeks after planting, and 4 weeks after planting), leaf area, wet weight and root length. Keywords: mycorrhiza, NPK, sweet mustard